The Lithuanian Computer Society’s learning section: five years of activity - Dagys, Viktoras (Information & Media, 1997)
The article is devoted to the activities of the Lithuanian Computer Society’s Learning Section. The Lithuanian Computer Society is a voluntary, initiating, professional, and creative public organization of programmers and hardware specialists. Members of this Society can form special interest groups (sections). The Learning Section unites Computer Science teachers from secondary schools and universities, and computer education specialists from the Ministry of Education and Science. The fields and forms of activity in 1991-1996 are presented.